Legal protection of air pollution in Iraq - Ashour, Ameel Jabbar; Abdul Wahab, Harlida (Diyala University, 2016)
One of the major challenges to protect the environment in Iraq is air pollution.As it has become a great problem in Iraq and is of great concern due to its negative effects on the quality of life.Air pollution reduces renewable and non-renewable natural sources and is a major threat to the life of the coming generations. Environmental experts agree that the current environmental problems in Iraq are the result of three great wars; all kinds of internationally prohibited weapons were used by, Saddam Hussein, the previous Iraqi regime.Needless to say, the effect of the Second Gulf War on the environment in Iraq and other neighboring countries in 1991 is equal to the great environmental pollution resulting from the explosion of the Nuclear Chernobyl Reactor in the Soviet Union in 1986.That war damaged the coastal areas in some countries, led to the increase of earth’s temperature and the pollution of water and air due to a massive oil leak and widespread fires in the oil wells. The estimated leak from the shipping stations and sinking ships was about 8.4 million barrels.It is worth noting that the environment was not just affected by one kind of pollutant, but also involved radio logical, chemical and other electromagnetic pollutants.This accident negatively affected the lives of people, especially those residing in the affected area.Furthermore, the United States' occupation to Iraq in 2003 had a crucial role in increasing the problem of environmental air pollution; they used internationally prohibited weapons, e.g., radioactive uranium and chemical weapons.The use of such weapons led to fatal health problems for the Iraqi people, evidenced mainly by the occurrence of cancerous diseases, distorted new born babies and infertility.Hence, this paper proposes the adoption of the Iraqi criminal law represented by the Iraqi Punishments Law No. 111 of 1969, is a law governing all crimes without exception, whether they are environmental or ordinary crimes. Additionally, the special law of the environment represented by the law of protecting and improving the environment No. 13 in 1997 was amended by Law No. 27 in 2009.Many provisions under this law legislate the protection of the environment from air pollution crimes and the protection of individuals and cities by criminalizing every act that constitutes an assault to the environment. For this purpose, a qualitative method of research is adopted as primary and secondary sources were consulted.